Consuming empire in US fiction, 1865-1930 - Wayne, Heather Diane (Edinburgh : Edinburgh University Press, 2023)
Traces authors' attitudes toward US economic expansionism through their fictional allusions to internationally-traded commodities.
Introduction : Getting to know the inter-imperial "lineages" of domestic commodities in US Fiction, 1865-1930 -- 1. Cotton, carmine, coal, and flour : The ethics and aesthetics of domestic consumption in Alcott and Phelps -- 2. Maneuvering through centuries of inter-imperial fur trading and gold speculation in Woolson and Ruiz de Burton -- 3. Bouguereau is best : Disentangling economic and aesthetic values in Norris and Du Bois -- 4. Orientalist consumption of pearls and blue Chinese porcelain in Wharton and Larsen -- Conclusion.
Includes bibliographical references and index.
Heather Wayne is a teacher of English and independent researcher living in Massachusetts. She earned her Ph.D. from the University of Massachusetts Amherst, and she has taught writing and literature courses at UMass Amherst and the University of Central Florida. Her research focuses on nineteenth-century US literature, material culture, feminism, visual culture, empire and global history.
Print version record.
JSTOR
Keywords: American fiction -- 19th century -- History and criticism; American fiction -- 20th century -- History and criticism; Imperialism in literature; Commercial products in literature; Consumption (Economics) in literature; Roman américain -- 19e siècle -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Impérialisme dans la littérature.; Produits commerciaux dans la littérature.; LITERARY CRITICISM / American / General; American fiction; Commercial products in literature; Consumption (Economics) in literature; Imperialism in literature; 1800-1999; Criticism, interpretation, etc; Literary criticism; Literary criticism; Critiques littéraires.